Externalities of local partnerships in a Subsistence Context - Francisco Cláudio Freitas Silva; Ramon Silva Leite (Gestão & Regionalidade)
Discerning the consequences of local partnerships in the context of subsistence is opportune, considering the various resource deficits that these markets present. The present study analyzes the concept of externalities in a subsistence context featuring local partnerships. We conducted an ethnographic inspired research using a bottom-up approach on raffler trips - a contemporary peddler activity - in two states from different Brazilian regions, to observe the exchange relations between the raffler and its local partners. We found that transactional flexibility and sociality are important mechanisms for the success of these relationships. With that, there is a stimulus to consumption by remote communities and generation of employment, income and occupation. However, local partnerships in subsistence markets also cause barriers to local businesses and present conflicting business relationships and financial risks. Examining the consequences related to local partnerships in subsistence marketplaces contributes by connecting the externalities construct to a subsistence perspective.